Reduction of Melatonin Level in Patients with Type II Diabetes and Periodontal Diseases - Hamidreza Abdolsamadi; Mohammad Taghi Goodarzi; Fatemeh Ahmadi Motemayel; Mina Jazaeri; Javad Feradmal; Mahdiyeh Zarabadi; Mostafa Hoseyni; Parviz Torkzaban (Tabriz University of Medical Sciences, 2014)
Background and aims. Melatonin is a circulating hormone that is mainly released from the pineal gland. It possesses antioxidant, free-radical scavenging, and immune-enhancing properties. A growing number of studies reveal a complex role for melatonin in influencing various diseases, including diabetes and periodontal diseases. The aim of this study was to ex-amine the possible links between salivary melatonin levels and type II diabetes and periodontal diseases. Materials and methods. A total of 30 type II diabetic patients, 30 patients with periodontal diseases, 30 type II diabetic patients with periodontal disease and 30 age- and BMI-matched controls were studied. The periodontal status was evaluated by the Community Periodontal Index (CPI). Salivary melatonin levels were determined by a commercial enzyme-linked immunosorbent assay (ELISA) kit. Results. The mean of salivary melatonin level was significantly lower in patients with either periodontitis or diabetes com-pared to healthy subjects (P < 0.05). Salivary melatonin concentration decreased in type II diabetic patients and periodontitis patients, and then decreased reaching the lowest levels in type II diabetic patients with periodontal disease. Conclusion. Based on the results of this study, it can probably be concluded that salivary level of melatonin has an impor-tant role in the pathogenesis of diabetes and periodontal diseases. It is also worth noting that this factor could probably be used as a pivotal biological marker in the diagnosis and possible treatment of these diseases, although further research is required to validate this hypothesis.